EVALUASI EKONOMI PENGGUNAAN ALAT PENGERING HIBRID TIPE RAK UNTUK PENGERINGAN KERUPUK RAMBAK - , YUYUN KUSUMAWATI; , Dr. Ir. Bandul Suratmo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The drying process of kerupuk was performed by Small and Medium Enterprises (SMEs) âHappyâ in Bayanan, Gesikan, Gantiwarno Klaten district in Central Java was using hybrid dryer rack type. The drier a beam size of 220 cm Ã 448 cm Ã 305 cm form bricks and cement. This room has been modified by adding ventilator and heat exchanger to circulate the dry air from the furnace. This research was intended to evaluate the feasibility of the hybrid drier for drying kerupuk in terms of economic aspects. Evaluation will be done is by comparing the cost of drying that uses direct sunlight and using dryers drying hybrid. Economic analysis will be used to study the feasibility of the hybrid dryer rack type can use the analysis of the Net Present Value (NPV), Break even analysis, and analysis of Benefit Cost Ratio (BCR). The results obtained from this analysis is the NPV = Rp 143.827.175,74, BCR = 1,61, and BEP = at least 4 times the drying / rainy season.